A note on the Wilhelmine Inconsistency. (8th February 2022) - Litland, Jon Erling
Abstract: Wilhelm has recently shown that widely accepted principles about immediate ground are inconsistent with some principles of propositional identity. This note responds to this inconsistency by developing two ground-theoretic accounts of propositional individuation. On one account some of the grounding principles are incorrect; on the other account, the principles of propositional individuation are incorrect.